Use of a beta-lactam graded challenge process for inpatients with self-reported penicillin allergies at an academic medical center - Sunagawa, Shawnalyn W.; Bergman, Scott J.; Kreikemeier, Emily; Watkins, Andrew B.; Alexander, Bryan T.; Miller, Molly M.; Schroeder, Danny; Stohs, Erica J.; Van Schooneveld, Trevor C.; May, Sara M. (Frontiers in Allergy, 2023)
Background The Antimicrobial Stewardship Program (ASP) at Nebraska Medicine collaborated with a board-certified allergist to develop a penicillin allergy guidance document for treating inpatients with self-reported allergy. This guidance contains an algorithm for evaluating and safely challenging penicillin-allergic patients with beta-lactams without inpatient allergy consults being available. Methods Following multi-disciplinary review, an order set for beta-lactam graded challenges (GC) was implemented in 2018. This contains recommended monitoring and detailed medication orders to challenge patients with various beta-lactam agents. Inpatient orders for GC from 3/2018–6/2022 were retrospectively reviewed to evaluate ordering characteristics, outcomes of the challenge, and whether documentation of the allergy history was updated. All beta-lactam challenges administered to inpatients were included, and descriptive statistics were performed. Results Overall, 157 GC were administered; 13 with oral amoxicillin and 144 with intravenous (IV) beta-lactams. Ceftriaxone accounted for the most challenges (43%). All oral challenges were recommended by an Infectious Diseases consult service, as were a majority of IV challenges (60%). Less than one in five were administered in an ICU (19%). Almost all (n = 150, 96%) were tolerated without any adverse event. There was one reaction (1%) of hives and six (4%) involving a rash, none of which had persistent effects. Allergy information was updated in the electronic health record after 92% of the challenges. Conclusion Both intravenous and oral beta-lactam graded challenges were implemented successfully in a hospital without a regular inpatient allergy consult service. They were well-tolerated, administered primarily in non-ICU settings, and were often ordered by non-specialist services. In patients with a self-reported penicillin allergy, these results demonstrate the utility and safety of a broadly adopted beta-lactam GC process.